2003
DOI: 10.1207/s15327663jcp1304_07
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virtual Experience in Consumer Learning

Abstract: Through a series of studies designed to explore important aspects of virtual experience, a new type of product affordances—virtual affordances—is proposed and tested empirically. In addition, the existing geometric and material product taxonomy is extended to include mechanical products within the classification structure. Utilizing these new concepts, 3‐D product visualization is compared with traditional 2‐D product representations and television advertising. The results largely support the proposition that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 56 publications
9
146
0
1
Order By: Relevance
“…Following the logic of the hierarchy of effects model (Lavidge and Steiner, 1961), exposure to a rotating, online product presentation would evoke affective and cognitive responses in consumers and culminate in a conative response. Similarly, Li et al (2003) proposed that a 3-D product presentation with rotation may create all of cognitive, affective, and conative responses.…”
Section: Consumer Response Systemmentioning
confidence: 99%
“…Following the logic of the hierarchy of effects model (Lavidge and Steiner, 1961), exposure to a rotating, online product presentation would evoke affective and cognitive responses in consumers and culminate in a conative response. Similarly, Li et al (2003) proposed that a 3-D product presentation with rotation may create all of cognitive, affective, and conative responses.…”
Section: Consumer Response Systemmentioning
confidence: 99%
“…(Li, Daugherty, & Biocca, 2003) [27] proposed that virtual experience is a psychological state which consumers interacts with the commodity in the virtual environment. (Marzocchi, Pizzi, & Scarpi, 2016)'s [28] study showed that the realization of consumer virtual experience is affected by objective factors, sensory factors, perceptual factors, stimulating response factors, cognitive and affective factors, encounter factors.…”
Section: The Relationship Between Group-buying Servicescape and The Vmentioning
confidence: 99%
“…Therefore, it is vital for online stores to consider using 3D technology with high interaction to present virtual products online. Specifically, Li et al found that 3D product presentations outperformed 2D pictorial presentations in enhancing perception of virtual product experience online [13]. Based on those findings, researchers had emphasized on supporting high level of interactivity on virtual 3D products and facilitate users to manipulate essential functions of 3D products to simulate real shopping situations.…”
Section: Literature Review 21 Interactivity and Product Understandingmentioning
confidence: 99%